2018
DOI: 10.1111/jir.12471
|View full text |Cite
|
Sign up to set email alerts
|

Problem behaviours and psychotropic medication use in intellectual disability: a multinational cross‐sectional survey

Abstract: We found evidence of prevalent potential 'off-label' use for psychotropic medication, which may be due to PBs. We also found evidence of potential diagnostic-overshadowing, where symptoms of psychiatric co-morbidity may have been attributed to PBs. Our findings provide renewed importance, across borders and health systems, for clinicians to consider a holistic approach to treating PBs, and attempting to best understand the precipitants and predisposing factors before psychotropic prescribing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 17 publications
1
33
0
2
Order By: Relevance
“…An associated problem here is the challenge associated with what has been termed "diagnostic overshadowing" among people with intellectual disability (Prosser, Moss, Costello, Simpson, & Rowe, 1998), and the challenges associated with establishing a clinical diagnosis when the person has limited capacity to participate in a detailed assessment (White, Chant, Edwards, Townsend, & Waghorn, 2005). One consequence of this is that there is a risk that comorbid psychopathology may be overlooked by clinicians, and instead be attributed to the person's intellectual disability, and therefore go undiagnosed and underreported, and therefore untreated (Ali, 2008;Jones, Howard, & Thornicroft, 2008;Perry et al, 2018).…”
Section: The Prevalence Of Dual Disabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…An associated problem here is the challenge associated with what has been termed "diagnostic overshadowing" among people with intellectual disability (Prosser, Moss, Costello, Simpson, & Rowe, 1998), and the challenges associated with establishing a clinical diagnosis when the person has limited capacity to participate in a detailed assessment (White, Chant, Edwards, Townsend, & Waghorn, 2005). One consequence of this is that there is a risk that comorbid psychopathology may be overlooked by clinicians, and instead be attributed to the person's intellectual disability, and therefore go undiagnosed and underreported, and therefore untreated (Ali, 2008;Jones, Howard, & Thornicroft, 2008;Perry et al, 2018).…”
Section: The Prevalence Of Dual Disabilitymentioning
confidence: 99%
“…For example, Cooper, Smiley, Morrison, Williamson, and Allan () found that the point prevalence of mental illness among a Scottish population of 1,023 adults with intellectual disability varied from 15.7%, when assessed using Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition Text Revision (DSM‐IV‐TR) criteria, up to 40.9% when clinician‐rated diagnoses of mental illness were considered. Other recent research has cautioned that symptoms of potential comorbid psychiatric diagnoses could be being attributed to problem behaviours, with a recent study highlighting that problem behaviours are one of the most common reasons for the referral of people with intellectual disabilities to mental health services (Perry et al, ). These kind of observed differences in prevalence estimates were also demonstrated in a German study of 371 adults with intellectual disability that reported a point prevalence of diagnosed mental illness of 10.8% but a much higher rate (45.3%) of problem behaviours (Schutzwohl et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sebuah penelitian potong lintang multinasional pada pasien disabilitas intelektual menunjukkan bahwa penggunaan psikotropika adalah 90%, terutama antipsikotik yakni sebesar 74%. 20 Antipsikotik, terutama risperidon, dinilai efektif dalam mengurangi gangguan perilaku pada anak-anak dengan disabilitas intelektual. 21 Beberapa penelitian sebelumnya mengenai bukti efektivitas risperidon pada pasien anak dan remaja dengan disabilitas intelektual dengan atau tanpa gangguan penyerta menunjukkan bahwa obat tersebut mempunyai efektivitas dalam memperbaiki gangguan perilaku.…”
Section: Pembahasanunclassified
“…Clinicians may therefore decide to treat empirically based on symptoms suggestive of mental illness, sometimes due to diagnostic overshadowing or difficulties in making diagnoses (Perry et al . ). Having access to reliable tools to aid diagnosis and to identify subgroups that can be targeted with specific interventions, as well as to track treatment response may therefore improve optimisation of psychotropic medication prescribing in individuals with ID.…”
mentioning
confidence: 97%
“…Clinicians may therefore decide to treat empirically based on symptoms suggestive of mental illness, sometimes due to diagnostic overshadowing or difficulties in making diagnoses (Perry et al 2018).…”
mentioning
confidence: 99%